Amelia's book of notes & note passing - Moss, Marissa (New York : Simon & Schuster Books for Young Readers, 2006)
The hand-lettered contents of a nine-year-old girl's notebook, in which she records her thoughts and feelings about notes and friendship.
Keywords: Friendship -- Fiction; Diary fiction